Phenotyping calcium and contraction in a zebrafish model of phospholamban R9C mutation. (10th June 2022) - Vicente, M; Salgado-Almario, J; Collins, M M; Martinez-Sielva, A; Valiente, A; Griesbeck, O; Vincent, P; Domingo, B; Llopis, J
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Ministry of Science, Innovation and Universities, Spain by Consejería de Educación, Cultura y Deportes. Junta de Comunidades de Castilla-La Mancha. Background: Phospholamban regulates SERCA2a pump activity by reducing its calcium affinity in the heart. Under β-adrenergic stimulation, protein kinase A (PKA) phosphorylates phospholamban attenuating its inhibitory effect on SERCA2a. The phospholamban mutation Arg 9 to Cys (R9C) was firstly identified in an American family with ventricular dilatation and premature death, and subsequently in a cohort of dilated cardiomyopathy patients in South Africa. Emerging evidence suggests that phospholamban R9C is a loss-of-function mutation with autosomal dominant inheritance. In vitro studies revealed that it enhances pentamer assembly by disulfide bridge formation, reducing the availability of phospholamban monomers to regulate SERCA2a. Purpose: The present study aimed to investigate defects in Ca2+ handling and cardiac function of phospholamban R9C mutation in an in vivo zebrafish model. Methods: We generated transgenic zebrafish lines overexpressing phospholamban wild-type (TgPLNwt) and phospholamban R9C (TgPLNR9C) in the heart of zebrafish. To measure calcium kinetics in 3 day-old larvae, TgPLNwt and TgPLNR9C fish were outcrossed with transgenic zebrafish lines expressing the fluorescent calcium biosensor mCyRFP1-GCaMP6f (TgRFP-GcaMP6f) and the bioluminescence calcium biosensor GFP-Aequorin (TgGA) in the heart. Results: Overexpression of phospholamban wild-type and R9C did not alter the heart rate compared to sibling larvae, and no differences were observed in the upstroke and recovery time of the calcium transients. However, atrial and ventricular calcium transient amplitude were higher in TgPLNR9C larvae with respect to TgPLNwt larvae. Contractile force of the heart, assessed as the fractional shortening, increased in TgPLNR9C larvae compared to siblings and TgPLNwt. Furthermore, stroke volume and cardiac output were also higher in TgPLNR9C larvae. Bioluminescence experiments were performed to estimate the average calcium levels in the heart. We found that TgPLNR9C larvae showed higher calcium levels than sibling and TgPLNwt larvae. To evaluate the responsiveness to β-adrenergic stimulation, larvae were treated with the β-agonist isoproterenol. Calcium transient amplitude and contractile force increased in sibling and TgPLNwt larvae after treatment. However, this response was absent in TgPLNR9C larvae, suggesting that they were hyper-stimulated in basal conditions, displaying amplitude and contractile force similar to sibling and TgPLNwt larvae treated with isoproterenol. Conclusion: TgPLNR9C larvae exhibited aberrant calcium handling in the heart with higher calcium levels and contractility, consistent with a lack of inhibition of SERCA2a. Consequently, TgPLNR9C larvae did not respond to β-adrenergic stimulation. These results were consistent with previous in vitro studies carried out in cardiomyocites infected with phospholamban R9C and highlighted the pathological defects of phospholamban R9C at early stages of the disease.